The Role of Microelements of Lumbar Disc Degeneration in Patients Undergoing Lumbar Spine Surgery - Sadiq R. Karkush; Manal K. Rasheed; Ali T. Abdul Wahid; Ahmed R. Majeed (مجلة كلية الطب)
Background: Lumbar disc degeneration (LDD) is a common musculoskeletal disorder that frequently causes low back pain (LBP). In addition to the discomfort of lower back pain, it can accompany pain in one or both legs. The lumbar spine and sacrum, consisting of five vertebrae and one bone, determine the spine's balance. Microelements are essential in bone metabolism and are associated with the prevention of osteoporosis and the alleviation of musculoskeletal pain.